Pengembangan Perangkat Pembelajaran Berbasis Authentic Problem Inquiry Terhadap Keterampilan Proses Sains Peserta Didik Kelas X pada Materi Ekosistem - Putu Lia Rusita Dewi; Putu Budi Adnyana; Ajeng Purnama Heny (Universitas Pendidikan Ganesha, 2025)
This research aims to develop learning tools based on Authentic Problem Inquiry (API) to improve students' science process skills in ecosystem materials at the high school level. The background of this research is based on the importance of contextual learning that actively involves students in solving real problems, so that they are able to practice science process skills such as observing, classify, interpret, predict, plan, implement, and communicate. The method used is Research and Development (R&D) with a 4D development model (Define, Design, Develop, and Disseminate). The research subjects consisted of two validators, 12 students in a limited trial, and four Biology teachers as practical respondents. Data collection techniques include expert validation, instrument trials, and practicality questionnaires. The results of the study showed that the teaching modules and LKPD developed were very valid with a Gregory validity value of 1.0. The science process skill test instrument showed very high reliability (coefficient of 0.883). In addition, the results of the practicality test show that the product is very practical to use in learning. The implications of this study indicate that the application of API-based teaching modules is able to provide a meaningful learning experience, increase active student involvement, and develop science process skills effectively according to the demands of the Independent Curriculum and 21st century learning.